The implementation of Balanced Scorecard System in social enterprises using the social-cooperatives – compliance with the needs of external organisations - Szemán, Judit; Musinszki, Zoltán; Bozsik, Sándor (International Journal of Engineering and Management Sciences, 2020)
To discover the major economic problems of social cooperatives, we have made a survey. The analysis of this survey stated that the quality of available labour force and the finding of the proper target markets are the biggest concerns of social cooperatives. By this survey a Balanced Scorecard model (BSC) was implemented, which is an adaptation of Bull’s model (Bull, 2006). Present paper demonstrates the BSC modul to satisfy the needs of external partners and authorities. These needs and the tracing indicators were determined, furthermore the frequency of the indicator measurement was also proposed.